A Case of Right Sided Strangulated Obturator Hernia: An Extremely Rare Type of Hernia Managed - Hamal, B K; Thapa, Ganesh; Karmacharya, B G (Medical Journal of Shree Birendra Hospital, 2003)
A Case of Right Sided Strangulated Obturator Hernia: An Extremely Rare Type of Hernia Managed